The Chase - Mills, DiAnn (Grand Rapids, Mich. : Zondervan, 2012)
Kariss' dream of being a crime writer causes her to look at the cold case of a young child found in the woods starved to death, but after enlisting the help of FBI Agent Tigo Harris, she and Tigo find themselves in a dangerous situation as they try to solve the crime.
Keywords: Murder -- Fiction -- Investigation; Child abuse -- Fiction; Houston (Tex.) -- Fiction; Christian fiction; Suspense fiction